2021
DOI: 10.1017/s000711452100146x
|View full text |Cite
|
Sign up to set email alerts
|

Genetically determined variations of selenoprotein P are associated with antioxidant, muscular, and lipid biomarkers in response to Brazil nut consumption by patients using statins

Abstract: Several single nucleotide polymorphisms (SNPs) could indirectly, as well directly, influence metabolic parameters related to health effects in response to selenium (Se) supplementation. This study aimed to investigate whether the selenoprotein SNPs were associated with the response of Se status biomarkers to the Brazil nut consumption in patients using statins and if the variation in Se homoeostasis could affect antioxidant protection, lipid profile, muscle homoeostasis and selenoproteins mRNA. The study was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Diverse relationship between plasma selenium level and SELENOP polymorphism with various metabolic syndrome (MetS) including obesity, hypertriglyceridemia and high density lipoprotein cholesterol has been found indicating GA + AA and GA genotype of SELENOP rs7579 variant signi cantly associated with increased risk of MetS [34]. Similarly, mRNA expression among individuals with GG genotype carrier for rs7579 variant was found lower before and after Brazil nut consumption [53]. However, in present study SELENOP rs9686343 signi cantly associated with PCOS as indicated by OR, allele C act as risk factor for PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…Diverse relationship between plasma selenium level and SELENOP polymorphism with various metabolic syndrome (MetS) including obesity, hypertriglyceridemia and high density lipoprotein cholesterol has been found indicating GA + AA and GA genotype of SELENOP rs7579 variant signi cantly associated with increased risk of MetS [34]. Similarly, mRNA expression among individuals with GG genotype carrier for rs7579 variant was found lower before and after Brazil nut consumption [53]. However, in present study SELENOP rs9686343 signi cantly associated with PCOS as indicated by OR, allele C act as risk factor for PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…Another study in pregnant women from the United Kingdom showed that, under Se supplementation during pregnancy, the rs3877899 A allele helped to maintain the Se status at a constant level, though the activity of GPX3, another circulating selenoprotein, increased [ 123 ]. Moreover, SELENOP rs3877899 altered the LDL levels in response to Brazil nut intake, suggesting that SELENOP polymorphisms affected the ability of Se to improve lipid biomarkers [ 124 ]. In general, very few studies have considered variations in SELENOP in its association with GLMDs, which needs more attention in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there were benefits of the consumption of one Brazil nut/day for three months on the selenium status, oxidative stress, body weight, and muscle parameters by patients using statins [98]. Additionally, a single nucleotide variation in the gene for selenoprotein P was associated with antioxidant, muscular, and lipid biomarkers in response to Brazil nut consumption by patients using statins, highlighting the role of individual variation in the metabolic response to selenium intake [110]. These approaches for selenium supplementation substantiate the relevance of Brazil nut on assisting in health outcomes and support the promotion of a local product originating from the Brazilian Amazon to improve selenium deficiencies derived from obesity in the Brazilian population.…”
Section: Selenium Supplementation and Sams In Brazilmentioning
confidence: 99%